Letter from Carl Duncan to Patricia Whiting, August 29, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan recounts a conversation he had with Whiting in which she offered to make him a shirt from her new sewing machine.